2003
DOI: 10.1007/s00442-003-1369-2
|View full text |Cite
|
Sign up to set email alerts
|

C 4 grasses in boreal fens: their occurrence in relation to microsite characteristics

Abstract: C(4) plants are rare in cool climates, an ecological pattern attributable to their poor photosynthetic performance at low temperatures relative to C(3) species. However, some C(4) species are able to persist at high latitudes and high elevations, possibly due to the characteristics of the particular microsites they inhabit in these otherwise unfavourable environments. One such species is Muhlenbergia glomerata, which occurs above 60 degrees N in Canada and is found in the atypical C(4) habitat of boreal fens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The high WUE i of D. villosum could be attributed to g s or to higher P N or even in a combination of both (Tambussi et al 2007). However, specific microclimatic characteristics may thus enable the C 3 species to persist, and even outcompete the C 4 species (Kubien and Sage 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The high WUE i of D. villosum could be attributed to g s or to higher P N or even in a combination of both (Tambussi et al 2007). However, specific microclimatic characteristics may thus enable the C 3 species to persist, and even outcompete the C 4 species (Kubien and Sage 2003).…”
Section: Discussionmentioning
confidence: 99%
“…At the southern extremes of the boreal zone, C. canadensis generally emerges very soon after snowmelt in early April and senesces by mid to late August, whereas M. glomerata does not typically emerge until late May and remains active until late September (D.S.K., personal observation). Following severe winters, high water levels in the fens occupied by C. canadensis and M. glomerata can delay formation of the C 3 canopy until relatively late into the spring (Kubien & Sage 2003). In the simulation shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, C 3 plants have a higher maximum quantum yield ( φ CO2 , the linear region of the light‐response curve) than C 4 plants when measured below 23 to 30 °C (Ehleringer & Björkman 1977; Ehleringer & Pearcy 1983), and this may allow C 3 plants to have higher rates of carbon gain when light is limiting at low temperatures (Ehleringer 1978). Despite these fundamental limitations, some C 4 species persist in high latitude or high elevation sites, indicating that C 4 photosynthesis is not inherently excluded from such areas (Schwarz & Redmann 1988; Sage & Sage 2002; Kubien & Sage 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1 were better adapted to arid environments. However, other studies have found that some C 4 grass communities' productivity increased relative to their competing C 3 equivalents with increased rainfall and in some cases are more abundant than C 3 grasses in wetland habitats (Epstein et al, 1997;Kubien and Sage, 2003;Paruelo et al, 1998;Paruelo and Lauenroth, 1996). Because it has been shown that C 3 and C 4 Poaceae (and Cyperaceae) distributions evolved in distinct geographical areas in Southern Africa, determined largely by growing season temperatures, and the interchanges between C 3 and C 4 plants are represented by archived δ 13 C wax values (Eglinton and Hamilton, 1967), a link can potentially be made between the changes in relative C 3 /C 4 proportions of OM input, substantiated by the palynology and physical peat forming processes archived in the Mfabeni peat deposit, and fluctuations in palaeotemperature and paleohydrology at the time of sedimentation.…”
mentioning
confidence: 99%